Overtraining in resistance exercise: An exploratory systematic review and methodological appraisal of the literature - Grandou, C.; Wallace, L.; Impellizzeri, F. M.; Allen, N. G.; Coutts, A. J. (Sports Medicine, 2020)
Background: The balance between training stress and recovery is important for inducing adaptations to improve athletic performance. However, continuously high training loads with insufficient recovery may cause fatigue to accumulate and result in overtraining. A comprehensive systematic review is required to collate overtraining literature and improve the current understanding of the mechanisms underlying functional overreaching (FOR), non-functional overreaching (NFOR) and the overtraining syndrome (OTS) in resistance training. Objective: The objective of this systematic review was to establish markers of overtraining and elucidate the mechanisms underlying maladaptive resistance training conditions. Furthermore, this review aims to critically evaluate the methodological approaches of the overtraining literature. Methods: A systematic literature search was performed on PubMed, Web of Science and SPORTDiscus to identify studies up to June 2019. Electronic databases were searched using terms related to resistance training and overtraining. Records were included if they attempted to induce a state of overreaching or overtraining through resistance exercise in healthy participants. Results: A total of 22 studies were selected for review. Among these studies, eight resulted in decrements in performance and measured changes in performance during a follow-up period. There were four studies that reported decrease in performance yet failed to implement follow-up measures. A total of 10 studies reported no decline in performance. Overall, a lack of standardisation in methodology (follow-up performance testing) and diagnostic criteria prevents consistent determination of FOR, NFOR and OTS in resistance training. Conclusions: Few studies have appropriately established FOR, NFOR or OTS in resistance training. Overtraining may be related to frequent high-intensity and monotonous resistance training. However, no marker other than a sustained decrease in performance has been established as a reliable indicator of overtraining in resistance exercise.